2011
DOI: 10.5194/hessd-8-7947-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictability of soil moisture and river flows over France for the spring season

Abstract: Sources of spring predictability of the hydrological system over France were studied on a seasonal time scale over the 1960–2005 period. Two random sampling experiments were set up in order to test the relative importance of the land surface initial state and the atmospheric forcing. The experiments were based on the SAFRAN-ISBA-MODCOU hydrometeorological suite which computed soil moisture and river flow forecasts over a 8-km grid and more than 800 river-gauging stations. Results showed that the predictability… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This could be due to a persistence of the skill from the previous winter through the land surface memory (i.e. groundwaterdriven streamflow or snowmelt-driven streamflow), as highlighted by Bierkens and van Beek (2009) Singla et al (2012) for parts of France, Lorenzo-Lacruz et al (2011) for the Iberian Peninsula and Meißner et al (2017) for the Rhine. Moreover, it could be that most of the gained predictability occurs in March, a transition month between the more predictable winter (as mentioned above) and spring, as discussed by Steirou et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to a persistence of the skill from the previous winter through the land surface memory (i.e. groundwaterdriven streamflow or snowmelt-driven streamflow), as highlighted by Bierkens and van Beek (2009) Singla et al (2012) for parts of France, Lorenzo-Lacruz et al (2011) for the Iberian Peninsula and Meißner et al (2017) for the Rhine. Moreover, it could be that most of the gained predictability occurs in March, a transition month between the more predictable winter (as mentioned above) and spring, as discussed by Steirou et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…While climate-model-based seasonal streamflow forecasting experiments are more common outside of Europe, for example for the United States (Wood et al, 2002(Wood et al, , 2005Mo and Lettenmaier, 2014), Australia (Bennett et al, 2016), or Africa , they remain limited in Europe, with a few examples in France (Céron et al, 2010;Singla et al, 2012;Crochemore et al, 2016), in central Europe (Demirel et al, 2015;Meißner et al, 2017), in the United Kingdom Prudhomme et al, 2017) and at the global scale (Yuan et al, 2015a;Candogan Yossef et al, 2017). This is because, although the quality of seasonal climate forecasts has increased over the past decades, there remains limited skill in seasonal climate forecasts for the extra-tropics, particularly for the variables of interest for hydrology, notably precipitation and temperature (Arribas et al, 2010;DoblasReyes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One common problem encountered in hydrologic forecasting studies is the requirement of obtaining adequate initial state variables that represent the hydrologic state of the catchment at the time of forecast. To eliminate the initial mismatch between observed and simulated hydrologic conditions (flow and state variables), many studies implement a pseudo‐observed discharge that is typically a hydrologic model simulation produced by forcing the model with observed meteorological data (Bierkens & van Beek, 2009; Greuell et al, 2018; Shukla & Lettenmaier, 2011; Shukla et al, 2014; Singla et al, 2012). By doing so, the pseudo‐observations are always perfectly matched by the hydrologic model as they stem from the same source.…”
Section: Models and Datamentioning
confidence: 99%
“…Similar to ESP, the CM‐SHF also heavily relies on the ICs, i.e., the anomalies from initial soil moisture and snow etc. Unlike quantifying the contribution of ICs to seasonal climate predictability using land–atmosphere‐coupled modeling approaches, the contribution of ICs to seasonal hydrologic predictability is often investigated using hydrologic models in a standalone mode . One of the theoretical frameworks to separate the contributions of ICs and atmospheric boundary forcings is called reverse ESP (revESP) .…”
Section: Sources Of Seasonal Hydrologic Predictabilitymentioning
confidence: 99%
“…As an important land surface storage term, snow has long been recognized as a major source of seasonal hydrologic predictability, particularly over high altitude and high latitude regions, where its impact can last for 3–6 months especially during cold seasons . Because of the strong control from snow, the climate forecasts of temperature could be as important as precipitation for streamflow forecast in high‐latitude snow‐fed river basins through the temperature–snow melt relationship .…”
Section: Sources Of Seasonal Hydrologic Predictabilitymentioning
confidence: 99%